Impact of water pollution on human health and environmental sustainability - McKeown, Elaine 1950-; Bugyi, George 1940- (Practice, progress and proficiency in sustainability (PPPS) books series, 2016)
This book highlights several important water-related issues and explores a number of potential solutions to the problem of water sustainability by focusing on research-based perspectives on water availability, industrial and agricultural pollution, water contamination, and their impacts on the human population as well as the environment.